The Entrepreneurial Intellectual in the Corporate University - Barrow, Clyde W. (Springer International Publishing, 2018)
This book presents a critical analysis of the corporate university. The author's personal narrative unfolds between the reality of the corporate university and the rhetoric of the entrepreneurial university, which allows the author to reveal how the corporate university is structurally antagonistic to the activities of entrepreneurial intellectuals. The book not only explores the internal contradictions of the corporate university, but the complicity of its bureaucratized intellectuals in reproducing the iron cage of bureaucracy. Drawing on the legacy of Pierre-Joseph Proudhon, Barrow argues that entrepreneurial intellectuals, whether as individuals or in small groups, must take direct action to improve their own conditions by steering a tenuous course between the market and the state.